IMPLEMENTATION OF SIMPLE MEDICAL CHEKUP ON RESIDENTS OF RW 06, JATIWARNA, PONDOK MELATI, BEKASI - Liza Laela Abida; Citra Amaniah Anhar; Ganesa Puput Dinda Kurniawan (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2022)
This community service is carried out for early prevention of non-communicable diseases and to determine the health status of the community in RW 06, Jariwarna, Pondok Melati, Bekasi. The method used in this community service has 3 stages, namely the survey stage, the preparation stage and the implementation stage. At the implementation stage there are 4 activities, namely checking blood pressure, checking fasting blood glucose, checking cholesterol and checking uric acid. The conclusion of this activity is that the average resident in RW 06 Jatiwarna does not yet have a healthy diet, so the results of a simple medical checkup show that the results are increased in blood pressure by a percentage of 63%, fasting blood glucose by a percentage of 54%, cholesterol by a percentage of 62% . For the next activity, you can teach participants about the topic of healthy eating patterns.